Measurement of Interleukine-6 and C-reactive Protein in Serum of Patients on Amlodipine Therapy - Nahla O. TawÀk; Rana Kh. Atarbashe (University of Mosul, College of Dentistry, 2015)
Aims: The aims of this ﬆudy were to compare between the immunological parameters (serum interleukin-6 (IL-6) and c-reactive protein (CRP) of patients suﬀering from chronic cardiovascular diseases with amlodipine therapy and control group to determine the eﬀects of the drug on those parameters. Materials and Methods: The ﬆudy was conducted on 42 subjects, 27 patients already on amlodipine therapy, aged ranged between 34-75 years. Fifteen healthy subjects of the same age group participated in this ﬆudy as a control group. The screening by medical hiﬆory, examination (gingival enlargement scores) and blood samples to measure serum IL-6 and CRP was done once at base line visit. Results: The results obtained showed that amlodipine trherapy group had higher gingival overgrowth scores and immunological parameters than control group with signiﬁcant diﬀerence at (p<0.05), also there was positive correlation but not signiﬁcant between CRP in serum and IL-6 (p< 0.05). Conclusion: The ﬆudy concluded that there is a signiﬁcant diﬀerence in the GO score and immunological parameters in amlodipine therapy group as compared with healthy group.